Trait-based assessment of polychaete assemblages distinguishes macrofaunal community structure among four distinct benthic eco-regions on a shallow arctic shelf. (April 2023) - Charrier, Brittany R.; Danielson, Seth L.; Mincks, Sarah L.
Abstract: In a rapidly changing Arctic, effects of taxonomic and functional composition of infaunal benthic communities on ecosystem function are poorly characterized for many areas of the continental shelf environment. Infaunal macrobenthos perform essential ecosystem services in soft-sediment habitats, including sediment oxygenation, organic-matter burial, and nutrient regeneration. Changes in the distribution and composition of infauna are likely to impact these important processes. We investigated spatial patterns in macrofauna on the northern Bering and southern Chukchi Sea continental shelves in conjunction with a suite of environmental variables as part of the Arctic Shelf Growth, Advection, Respiration, and Deposition (ASGARD) project. Depth-stratified macrofauna samples (>500 μm) were collected from multi-cores in June 2017 and 2018. Abundance and biomass were recorded for broad taxonomic categories (phylum or class). Polychaetes were identified to family to capture well-described functional-trait information. Functional guilds were assigned to polychaete families, reflecting feeding mode, motility, and feeding structures. Macrofauna exhibited no significant spatial patterns when examined at higher taxonomic levels; however, analysis of polychaete families yielded three distinct station groups, and polychaete functional guilds yielded four distinct groups. These groups were aligned with variations in key habitat characteristics and suggest variation in ecosystem function across the study area. At sandy stations, tube-dwelling, particle-selective suspension and surface deposit feeders were relatively abundant, reflecting an advective system with moderate current speeds and low deposition. Sites with gravelly substrate and moderate levels of organic matter in deeper sediment layers likely experience sporadic organic-matter deposition and disturbance from scouring and were inhabited by larger-bodied species, including bivalves and subsurface deposit-feeding or carnivorous polychaetes. Muddy, offshore stations in the southern Chukchi Sea also contained large bivalves and large carnivorous polychaetes, with evidence of high bioturbation. At more coastal Chukchi Sea stations, macrofauna were dominated by small, motile polychaetes concentrated in the 1-cm surface layer, with indications of anaerobic conditions below. Overall, polychaete functional traits and vertical distribution reflected the quality and quantity of organic matter input and the depositional environment inferred from grain size and current speed, with implications for biogeochemical cycling in sediments.